An Analysis Of Solar Energy Potential Based On Methods Weibull And Reyleigh Using Data From Weather Station - Selly Annisa Binti Zulkarnain; Suwarno; Muhammad Fitra Zambak (INFOKUM, 2021)
Electrical energy is the primary need of the Indonesian people. Most of the electrical energy used comes from fossil energy such as fuel oil, gas, and coal. Fossil fuels themselves can cause environmental damage and include non-renewable energy, so it is necessary to study the potential for power plant development using alternative energy. This study discusses the analysis of the energy potential of natural resources, namely sunlight. Where the energy potential is carried out using 2 methods, namely the Weibull distribution and the Rayleigh distribution. The results showed that the Weibull distribution gave more accurate results than the Rayleigh distribution. It is known from the Mean square error value of the Weibull distribution that it was 6.4% in 2013 and 9.3% in 2014, and from the Rayleigh distribution, it was obtained 9% in 2013 and 18% in 2014.